Encyclopedia of Analytical Chemistry 2016
DOI: 10.1002/9780470027318.a0715.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Based Combustion Diagnostics

Abstract: In laser spectroscopy, the interaction of light emitted from various types of laser sources – tunable or nontunable in their output frequency – with the atomic or molecular species of interest is used to probe the sample through a variety of spectral responses. In order to perform laser spectroscopy, suitable laser sources must be selected, which meet the requirements of the chosen spectroscopic method. This means that the laser has to provide radiation in the wavelength range of interest, has the appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 264 publications
0
5
0
Order By: Relevance
“…With the benefits of high-precision, these methods have been used in many combustion studies. [3,4] However, the spatial resolution of these methods is weak due to a limited number of signal paths. For the three-dimensional (3-D) flame measurement, the active measurement techniques require a large number of signal projections of the flame.…”
Section: Introductionmentioning
confidence: 99%
“…With the benefits of high-precision, these methods have been used in many combustion studies. [3,4] However, the spatial resolution of these methods is weak due to a limited number of signal paths. For the three-dimensional (3-D) flame measurement, the active measurement techniques require a large number of signal projections of the flame.…”
Section: Introductionmentioning
confidence: 99%
“…Thermometric techniques providing accurate measurements with good spatial resolution and, with the ability to map the temperature field in turbulent flows are highly demanded. Several techniques have been developed for this purpose and reviews of thermometric techniques can be found in [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…CST is implemented by multiple line-of-sight tunable diode laser absorption spectroscopic (TDLAS) measurements governed by the Beer-Lambert law [20], [21]. When a laser beam at frequency v (cm −1 ) penetrates an absorbing gas sample with a path of length L (cm), the wavelength-dependent absorbance, α(v), is defined as…”
Section: A Mathematical Formulation Of Cstmentioning
confidence: 99%